Quantifying the degree of change in supply chain determinants and resilience during the 2014–2015 economic crisis and the COVID-19 pandemic: placing emphasis - R. S. Rogulin (Управление)
The study examines the management culture transformation in supply chains digitalisation. The hypothesis of the study was that the digitisation of culture in companies will become an important tool for optimising the internal and external environment in supply chain management, considering the needs of business, shareholders and society. The aim of the study is to identify the determinants of supply chain management that have changed against the backdrop of digitalisation. Using a conceptual approach, two crises in the context of supply chain management determinants were explored: the commodity price crisis (2014–2015) and the COVID-19 pandemic crisis (2020–2021). Three main determinants of management are considered: planning, tracking and reputation. The result of the initial conceptualisation is derived from reviews of case studies and pandemic resilience monitoring of the business environment and supply chain. A set of external and internal factors have been identified that each group of countries needs to develop in order to achieve sustainability in their local supply chains. The most important drivers of global supply chain resilience that need to be developed to offset the effects of major crises have been identified. The results of the study can be used for effective corporate governance practices and a better understanding of supply chain management culture in a digitalised and COVID-19 environment.